High internal phase oil-in-water emulsions stabilized by supercritical carbon dioxide extruded whey protein concentrate. (15th March 2022) - Javad, Sumera; Gopirajah, Rajamanickam; Rizvi, Syed S.H.
Highlights: WPC (80% protein) was extruded with Supercritical carbon dioxide to enhance its functionality in terms of its emulsifying capability at two pH values 3.0 and 5.4. HIPEs were prepared with functionalized whey protein (f-WPC80 pH 3.0 and 5.4) and proved to be superior emulsifying capability as compared to NaCas stabilized HIPEs. Interfacial rheology measurement discovered the importance of functionalization of whey protein for the elasticity of the oil–water interface. This supercritical carbon dioxide extruded WPC may be a replacement of NaCas to make nutritionally superior products with pH 3.0 and 5.4. Abstract: High Internal Phase Emulsions (HIPEs) were stabilized by functionalized whey protein concentrate (WPC-80). Functionalization of WPC-80 was done by supercritical CO2 assisted extrusion technology. HIPEs were formed by 80% oil and 1-4 wt% of control (untreated) whey protein concentrate, extruded/functionalized whey protein concentrates (f-WPC-80) at pH 3.0 and 5.4, and sodium caseinate (NaCas) separately and were characterized for their stability at two temperatures (25 and 40 °C) for 20 days. Results indicated that f-WPC-80-pH3.0 formed self-standing gels at 1 wt% concentrations which were more stable, without phase separation, than those stabilized by commercially used stabilizer NaCas and native c-WPC. At 4% concentration of f-WPC-80-pH3.0, the compressed droplets produced emulsions with self-standing and viscoelastic features. While control WPC-80, could not form stable HIPEs at any investigated concentrations. The reported high internal phase oil-in-water emulsions, offer a potential new system for delivery of nutritionally superior and clean-label products of commercial utility.